Reproductive features of the biology of some ticks of the family Ixodidae Murray, 1877 widespread in the southeast of the North Caucasus - A. M. Atayev; M. M. Zubairova; N. T. Karsakov (Российский паразитологический журнал, 2021)
The purpose of the research is study of some reproductive characteristics of the biology of ticks of the family Ixodidae which are widespread in the southeast of the North Caucasus.Materials and methods. In 2000–2010, 9 series of experiments were carried out in the conditions of the plain belt in Dagestan. The first, second, and third series of experiments were intended to find out the duration of the tick searching for a place to fix on the animal, the duration of the skin incised and the proboscis inserted into the wound, and the engorgement duration; and the fourth series was intended to clarify the tick wintering on the animal. Such experiments were performed on two-year-old calf bulls on the Educational and Experimental Farm of the Dagestan State Agrarian University with Boophilus annulatus, Rhipicephalus bursa, Hyalomma detritum, H. scupense, and H. anatolicum in 2000. Five hungry adult female ticks were placed onto all 5 calf bulls in the middle third of the neck. We conducted experiments on searching for a place for egg-laying, egg-laying duration in the environment, number of eggs in a clutch, duration of the larva formed and the hatching rate, distance of the larvae from the hatching place, and larvae death rate in five specially equipped sites of pastures of 1 m2 . Five adult female ticks of B. annulatus, R. bursa, H. detritum, H. scupense, and H. anatolicum were placed after engorgement in each biological site.Results and discussion. Ixodid ticks perform their natural physiological functions associated with feeding and reproduction with significant time fluctuations. The search for a place to fix on the animal took 4–8 hours; the skin incised and proboscis inserted in the wound took 2–5 hours; the engorgement took 4–6 hours; the search for an egg-laying place took 10– 22 hours; the egg-laying duration in the environment was 18–23 hours; the number of eggs in a clutch was 4–13K; the duration of the larva formed and the hatching rate was 10–15 days and 58.0–75% respectively; the distance of the larva from the hatching place was 0.5–1.5 m; death rate of the larva in captivity was 100%; and the tick wintering on the animal was near the neck, ears, in the dewlap, the flank and the udder. These features are typical for the analyzed tick species in the southeast of the North Caucasus and, probably, for other taxa of these genera.